Efektivitas Undang-Undang Dasar Tahun 1945 terhadap Mekanisme Checks and Balances dan Pemakzulan Presiden atau Wakil Presiden dalam Perspektif Hukum Tata Negara - Ayuningtiyas, Fitri; Khusnah, Aynul; Wahyuningtyas, Adelia (Universitas Muhammadiyah Yogyakarta, 2023)
The 1945 Constitution of the Republic of Indonesia outlines the impeachment mechanism. This Constitution outlines that the procedure for impeaching the president and vice president must be mandated by the People's Representative Council (DPR) to the People's Consultative Assembly (MPR). It is important to acknowledge that the current impeachment process upholds the principle of checks and balances of direct presidential elections. The impeachment decision of the current president and vice president cannot strengthen the rule of law when the Constitutional Court (MK) determines that the president or vice president has violated the Constitution. This research aimed to find out the impeachment mechanism outlined in the 1945 Constitution with the principle of the supremacy of constitutional law. This research included a qualitative method by focusing on the problematic effectiveness of the 1945 Constitution on the check and balance mechanism and the impeachment of the president and vice president from the constitutional law perspective. The check and balance mechanism aims to create a democratic government. Check and balance is a principle controlling and maintaining state institutions' balance. The results revealed that the 1945 Constitution's mechanism for impeaching the president or vice president was relatively ineffective because the rule of law and the constitutional judicial mechanism were still handled by the political mechanism. Consequently, the check and balance mechanism did not occur in this process. The characteristic of impeachment as a control causes impeachment cannot to be implemented following the rule of law, which was an indicator that the check and balance mechanism had been unbalanced by the Constitutional Court's decision, which was used to create a legal mechanism that was not explicit and binding on the MPR and the 1945 Constitution.